Patient activation is a treatable trait in patients with chronic airway diseases: An observational study - Peters, Jeannette B.; Antons, Jeanine C.; Koolen, Eleonore H.; van Helvoort, Hanneke A. C.; van Hees, Hieronymus W. H.; van den Borst, Bram; Spruit, Martijn A.; Vercoulen, Jan H.; van ’t Hul, Alex J. (Frontiers in Psychology, 2022)
Background: Self-management is key for reducing the burden of disease in chronical illness. However, applying self-management presupposes behavioral change. Sufficient knowledge, skills, confidence and motivation to make the needed behavior changes are important prerequisites. During the past years the Integral Diagnostic Trajectory was developed for patients with asthma or COPD which aims to identify treatable traits and activating patients for self-management. Objective: In the present study the effects of the Integral Diagnostic Trajectory on the Patient Activation Measure (PAM®) were examined. In addition, predictive variables for PAM baseline scores and change scores were sought. Materials and methods: A total of 241 patients with asthma or COPD referred to the pulmonologist at the Radboud university medical center, location Dekkerswald, Nijmegen were included. Patient activation was measured before the first visit and after the intervention with the 13-item Patient Activation Measure (PAM®). Additional, patient characteristics and health status were measured with the Nijmegen Clinical Screening Instrument (NCSI), modified Medical Research Council (mMRC), Asthma Control Questionnaire (ACQ), and COPD Clinical Questionnaire (CCQ). Results: Fifty percent of the patients with asthma and seventy percent of the patients with COPD had low levels of activation at baseline (PAM level 1-2). Baseline PAM scores could be explained in patients with asthma for 7% by number of severe problems in health status. And for 18% in patients with COPD by number of severe problems, age and employment status. After the intervention both groups significantly improved on the PAM (T0: 56.0 ±13.1 vs T1:63.3±14.0 in asthma, and T0: 50.0±8.8 vs 58.4± 11.1 in COPD). Multivariate stepwise regression analysis showed that only 24% of the change in score could be explained by baseline PAM score and being employed in patients with asthma, and 18% of the variance in change score could be predicted by baseline PAM score in COPD. Conclusion: The present study showed that low level of activation is a common feature in patients with asthma and COPD. With a relatively short and seemingly simple intervention patients can reach higher levels of patient activation, which is a prerequisite for adopting self-management techniques in daily life